Roxadustat (FG-4592) Facilitates Recovery From Renal Damage by Ameliorating Mitochondrial Dysfunction Induced by Folic Acid - Li, Xue; Jiang, Bo; Zou, Yu; Zhang, Jie; Fu, Yuan-Yuan; Zhai, Xiao-Yue (Frontiers in Pharmacology, 2022)
Incomplete recovery from acute kidney injury induced by folic acid is a major risk factor for progression to chronic kidney disease. Mitochondrial dysfunction has been considered a crucial contributor to maladaptive repair in acute kidney injury. Treatment with FG-4592, an inhibitor of hypoxia inducible factor prolyl-hydroxylase, is emerging as a new approach to attenuate renal damage; however, the underlying mechanism has not been fully elucidated. The current research demonstrated the protective effect of FG-4592 against renal dysfunction and histopathological damage on the 7th day after FA administration. FG-4592 accelerated tubular repair by promoting tubular cell regeneration, as indicated by increased proliferation of cell nuclear antigen-positive tubular cells, and facilitated structural integrity, as reflected by up-regulation of the epithelial inter-cellular tight junction molecule occludin-1 and the adherens junction molecule E-cadherin. Furthermore, FG-4592 ameliorated tubular functional recovery by restoring the function-related proteins aquaporin1, aquaporin2 and sodium chloride cotransporter. Specifically, FG-4592 pretreatment inhibited hypoxia inducible factor-1α activation on the 7th day after folic acid injection, which ameliorated ultrastructural abnormalities, promoted ATP production and attenuated excessive reactive oxygen species production both in renal tissue and mitochondria. This was mainly mediated by balancing of mitochondrial dynamics, as indicated by down-regulation of mitochondrial fission 1 and dynamin-related protein 1 as well as up-regulation of mitofusin 1 and optic atrophy 1. Moreover, FG-4592 pretreatment attenuated renal tubular epithelial cell death, kidney inflammation and subsequent interstitial fibrosis. In vitro, TNF-α-induced HK-2 cells injury could be ameliorated by FG-4592 pretreatment. In summary, our findings support the protective effect of FG-4592 against folic acid-induced mitochondrial dysfunction; therefore, FG-4592 treatment can be used as a useful strategy to facilitate tubular repair and mitigate acute kidney injury progression.